Retrospective study of severe acute malnourished children in nutrition rehabilitation center of Madhya Pradesh, India: Management and outcome - Bande, Bhushan Ashvinikumar; Thora, Sharad (Indian Journal of Child Health, 2019)
Introduction: Nutrition rehabilitation centers (NRCs) are established for optimal management of severe acute malnourished (SAM) children. Results of different NRCs vary in terms of outcome. Objective: The objective of the study was to know the morbidity and outcome pattern of SAM children. Materials and Methods: SAM children aged 0–59 months admitted during 2 years period in NRC of district hospital (secondary care center) of central India were enrolled in the study. Data of these children such as age, sex, weight on admission and discharge, complications, treatment, and outcome were studied. Results: A total of 993 children were admitted during 2 years April 2016–March 2018. Male children were 530 (53.37%) and female were 463 (46.62%). 93 (11.17%) children had mid-upper arm circumference <11.5 cm (<2 standard deviation [SD]), 464 (45.5%) were of <3SD and 436 (43.39%) were of < 4SD. A total of 49 (4.93%) children were aged <6 months, 366 (36.85%) between 7 and 12 months, 455 (45.82%) between 13 and 24 months, and 123 (12.38%) children were of >24 months of age. A total of 799 (80.46%) had associated medical complications and 521 (52.46%) children were admitted in the ward for stabilization and treatment of medical illness. 182 (18.32%) children were send back to corresponding NRC after stabilization while 50 (5.03%) were referred to a tertiary care center. From a total of 761 children in NRC, 594 (78.05%) improved, 60 (6.04%) were did not respond, 118 (15.5%) were defaulter, and 6 (0.6%) children died during treatment. The average duration of stay was 10.16 days and average weight gain was 10.01 g/kg/day. Conclusion: Besides, the target of reducing the prevalence of SAM, NRC is very important center for reducing under-five morbidity and mortality. To achieve the target to end up malnutrition, more NRCs should be started with the increasing capacity of existing NRCs with consideration of community-based model.